2016
DOI: 10.1007/s11085-016-9628-x
|View full text |Cite
|
Sign up to set email alerts
|

Metastable-Stable Phase Transformation Behavior of Al2O3 Scale Formed on Fe–Ni–Al Alloys

Abstract: The oxidation behavior of Ni-Fe-41.5at.%Al alloys with different Fe/Ni ratios was investigated in air at 1000°C in order to clarify the effect of Fe on the phase transformation of Al 2 O 3 scale, using in-situ high-temperature X-ray diffraction by means of synchrotron radiation. The oxidation mass gain of alloys after 25 h of oxidation generally decreased with increasing Fe content; however, the initial oxidation mass gain was significantly decreased by increasing alloy Fe content. Insitu X-ray diffraction ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Intermediate is the transformation from the mentioned initial transient oxide to the one that satises said local equilibrium conditions. 7,[14][15][16][17][18][19][20][21][22] The properties of the transient oxide are indeed crucial for the alumina forming process, partial control of which may be gained by the so-called 3rd element effect. As rst observed in the Cu-Zn-Al system, 23 the 3rd element effect is understood to initiate and maintain formation of a protective a-Al 2 O 3 scale.…”
Section: Introductionmentioning
confidence: 99%
“…Intermediate is the transformation from the mentioned initial transient oxide to the one that satises said local equilibrium conditions. 7,[14][15][16][17][18][19][20][21][22] The properties of the transient oxide are indeed crucial for the alumina forming process, partial control of which may be gained by the so-called 3rd element effect. As rst observed in the Cu-Zn-Al system, 23 the 3rd element effect is understood to initiate and maintain formation of a protective a-Al 2 O 3 scale.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 4.9 shows the phase transformation behaviour of Al2O3 scale which formed on Fe-41.5Al (at.%), Ni-41Al-41Fe (at.%) and Ni-41.5Al (at.%) [44]. It was found that high iron content is beneficial and promotes the rapid transformation to α-Al2O3.…”
Section: Metastable and Stable Alumina Scale Formationmentioning
confidence: 98%
“…From the previous studies, the template effect is interpreted as a precipitation of α-Al2O3 from the transient Fe2O3 with Al2O3 saturation [35,[40][41][42][43]. Hayashi et al [44] studied the meta-stable phase transformation behaviour of Al2O3 scale on Fe-Ni-Al alloys. They found that the oxidation mass gain tended to be reduced with the increased iron content in the alloy.…”
Section: Metastable and Stable Alumina Scale Formationmentioning
confidence: 99%